Rapid Detection and Isolation of Escherichia coli O104:H4 from Milk Using Monoclonal Antibody-coated Magnetic Beads - Luciani, Mirella; Di Febo, Tiziana; Zilli, Katiuscia; Di Giannatale, Elisabetta; Armillotta, Gisella; Manna, Laura; Minelli, Fabio; Tittarelli, Manuela; Caprioli, Alfredo (Frontiers in Microbiology, 2016)
Monoclonal antibodies (MAbs) specific for the lipopolysaccharide (LPS) of Escherichia coli O104:H4 were produced by fusion of Sp2/O-Ag-14 mouse myeloma cells with spleen cells of Balb/c mice, immunized with heat-inactivated and sonicated E. coli O104:H4 bacterial cells. Four MAbs specific for the E. coli O104:H4 LPS (1E6G6, 1F4C9, 3G6G7 and 4G10D2) were characterized and evaluated for the use in a method for the detection of E. coli O104:H4 in milk samples that involves antibody conjugation to magnetic microbeads to reduce time and increase the efficiency of isolation. MAb 1E6G6 was selected and coupled to microbeads, then used for immuno-magnetic separation (IMS); the efficiency of the IMS method for E. coli O104:H4 isolation from milk was evaluated and compared to that of the EU RL VTEC conventional culture-based isolation procedure. Milk suspensions also containing other pathogenic bacteria that could potentially be found in milk (Campylobacter jejuni, Listeria monocytogenes and Staphylococcus aureus) were also tested to evaluate the specificity of MAb-coated beads. Beads coated with MAb 1E6G6 showed a good ability to capture the E. coli O104:H4, even in milk samples contaminated with other bacteria, with a higher number of E. coli O104:H4 CFU reisolated in comparison with the official method (121 and 41 CFU respectively at 103 E. coli O104:H4 initial load; 19 and 6 CFU respectively at 102 E. coli O104:H4 initial load; 1 and 0 CFU respectively at 101 E. coli O104:H4 initial load). The specificity was 100%.